(3CMGOjK CHj GdLge GdYdGA Hf ehSi Hf YWjg GdHGgdjs - (3CHhGdLge GdYdGA Hf ehSi Hf YWjg GdHGgdjs
(3ChdgG (B:s
(3CNHQfG GdTjhN GdCFeI CHhfUQ ehSi Hf GdTjN GdYGQa CHj eMeO YHOGdbGOQ Hf CHj UGdM GdLjdj s
(3BNQgG (B:s
(3aEfj SeYJ ef QShd Gddg Udi Gddg Ydjg hSde MOjKkG de jefYfj SeYJg jbhd ef TgO Cf dG Edg EdG Gddg eNdUkG hKHJkG ef bdHg ONd GdLfI hde JeSg GdfGQ hGdMeO ddg QH GdYGdejf hUd Gddg Ydj SjO GdeQSdjf eMeO hYdi Bdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3Ydjg bQGAGJ hSeGYGJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK Mdje (B49) s
Keywords: (3GdMOjK h GdeUWdMs